Rancang Bangun Sistem Informasi Penilaian Kinerja Menggunakan Metode Management by Objective pada RRI Surabaya - Kurniawan, Hendra; Tanuwijaya, Haryanto; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: RRI Surabaya currently employs a total of more than 100 people consisting of civil servants and regular employees. RRI Surabaya seeks to improve the quality and quantity of work from each employee by conducting performance appraisals. In the performance appraisal which has been done so far, there are some shortcomings, namely: performance appraisal process takes too long and inefficient, no information is available about the performance of each employee in one period, there is no weighted value for each evaluation criteria in SKP evaluation and work behavior evaluation, the evaluation tends to be a subjective one, it is difficult to calculate how much time it takes to complete the work because of the absence of date recording when a task is given and also when the task is completed. To overcome these problems, RRI Surabaya needs a Performance Appraisal Information System using Management by Objective (MBO) Method. With the help of Performance Appraisal Information System using Management by Objective (MBO) Method is expected to produces more valuable informations about performance appraisal results. Keywords: Information System, Performance Appraisal, Management by Objective